2010
DOI: 10.1002/pssb.200983829
|View full text |Cite
|
Sign up to set email alerts
|

Role of S–Au labile bonding in stochastic switching of molecular conductance studied by STM

Abstract: We studied by scanning tunneling microscopy (STM) the stochastic switching of terthiophene-thiol (3T) molecules grafted on gold surface. For this purpose, 3T molecules were inserted in a dodecanethiol self-assembled monolayer (SAM).Results are analyzed and discussed in comparison with similar studies performed by other groups on various molecules. Stochastic switching events are attributed to S-Au bond fluctuation such as a breaking/reforming mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
0
6
0
2
Order By: Relevance
“…49,53 RTS has also been observed in single molecular junctions (STM). [55][56][57][58] In these experiments, the current fluctuations were ascribed to stochastic modifications of the conformation of the S-Au link at the molecule/Au interface. [55][56][57] Recently, STM experiments showed that these two-level fluctuations are not observed for molecule linked on hydrogenated Si through a Si-C bond, 58 mainly because the binding energy is larger for Si-C than for Au-S bonds.…”
Section: Proposed Mechanism and Discussionmentioning
confidence: 89%
“…49,53 RTS has also been observed in single molecular junctions (STM). [55][56][57][58] In these experiments, the current fluctuations were ascribed to stochastic modifications of the conformation of the S-Au link at the molecule/Au interface. [55][56][57] Recently, STM experiments showed that these two-level fluctuations are not observed for molecule linked on hydrogenated Si through a Si-C bond, 58 mainly because the binding energy is larger for Si-C than for Au-S bonds.…”
Section: Proposed Mechanism and Discussionmentioning
confidence: 89%
“…The XPS studies showed that on average only 3.2 out of the seven sulfur (S) moieties (anchoring groups) are bound to Au at any one time. Therefore, during the period of time that the STM measurement is performed, the number of S moieties of the β‐CD molecule bound to the Au surface could change, for example, from three S–Au interactions to four S–Au interactions, due to the labile bonding between the sulfur and the Au 38. Also, the sulfur moieties can have different adsorption geometries on the Au surface, which are directly related to the conductance through the anchoring groups of the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…random telegraph noise) due to sporadic configurational changes of the Au-S bond [17][18][19]. This effect is suppressed for SAMs on Si, because the Si-C or Si-O bonds have a larger binding energy [20] and it is only observed for single molecule with more free space around it [21].…”
Section: Chemistry and Self-assemblymentioning
confidence: 99%